The role of the resident nurse in the Covid-19 pandemics: Unveiling experiences and knowledge (Research, Society and Development, 2021)
The article aims to understand the experiences and knowledge reported by the Resident Nurse (RN) in the performance of the Covid-19 pandemic. This is an exploratory, descriptive social research, with a qualitative approach. This data was collected in November and December 2020, individually through a virtual questionnaire with open and closed questions, from which both objective and subjective data were generated, such as values, attitudes and opinions. The research was developed in accordance with the norms of Resolution 466/2012. The pandemic scenario in the in-service training units caused changes in the practical and theoretical context of the nursing residency, as the reports ranged from additional information about the Covid-19 to feelings faced by these professionals as well as suggestions for improving teaching strategies. The psychological damage of the ER was an interference very present in the daily lives of the interviewees. In addition, the pandemic has awakened in students the importance of using PPE’s during the provision of nursing care. It favored the insertion of technological advances to maintain the theoretical classes recommended by the course. With the pandemic, residents felt some gap in their learning resulting from adaptations aimed at online meetings, scale adaptation, practical training fields and opportunities for experiences of other pathologies. Thus, suggestions for improving the course were listed: training on Covid-19; reassessment of the themes of the theoretical classes so that they meet the nature of their activities in the practical field and psychological support during the development of the course.